Delay Factors in Building Construction Project of State Elementary School - Raden Risang Haryo C. D.; Lalu Mulyadi; Tiong Iskandar (Salehan Institute of Higher Education, 2020)
The state elementary school No.027 building construction project in Samarinda Ulu District, Samarinda City, Indonesia, in the 2019 fiscal year, which experienced delays, was allegedly due to the use of inappropriate scheduling methods. Therefore, to overcome these delays, it must use the curtain methods that are appropriate with efficient cost. In this study, we used factor analysis and multiple linear regression methods to measure answers from a questionnaire distributed to 45 respondents like consultants, contractors, and owners who were involved in the state elementary school in above. The results show that the elements that influence the delay in the construction of state elementary school building No.027 Samarinda is a factor in the work scheduling method and construction delay. For Scheduling work get a coefficient value is , and for construction delay method get a coefficient value is . It can be concluded is the most dominant factor construction delay in the State Elementary School No.027 Samarinda in case above is the Work Scheduling Method with a value coefficient is 1.057.